Chiropractic Treatment for Gastrointestinal Problems: A Systematic Review of Clinical Trials - E Ernst (Canadian Journal of Gastroenterology)
Many chiropractors believe that chiropractic treatments are effective for gastrointestinal disorders. The aim of the present systematic review was to critically evaluate the evidence from controlled clinical trials supporting or not supporting this notion. Six electronic databases were searched for relevant studies. No limits were applied to language or publication date. Prospective, controlled, clinical trials of any type of chiropractic treatment for any type of gastrointestinal problem, except infant colic, were included. Only two trials were found – one was a pilot study, and the other had reached a positive conclusion; however, both had serious methodological flaws. There is no supportive evidence that chiropractic is an effective treatment for gastrointestinal disorders.